THE GUARDIAN OR THE GRANTOR: THE ROLE OF NARCISSISTIC PERSONALITY AND MORAL REASONING IN AUDIT RISK - Nabiilah Putri; Diendha Annisa Nur Attaullah; Yusnaini Yusnaini (Jurnal Media Akademik (JMA), 2026)
Auditors play a crucial role as "guardians" of financial statement integrity. However, audit practices reveal that auditors are not always independent; they can even become "licensors" who allow manipulation to occur. This article aims to analyze the dual role of auditors by examining the influence of narcissism and moral reasoning on audit risk. Through a systematic literature review of 40 Scopus and SINTA-indexed scientific publications (2021-2025), this study examines behavioral factors and personal characteristics that influence the quality of auditor decisions. Findings reveal that narcissism has a paradoxical effect: enhancing professional skepticism while simultaneously creating conflicts of interest and reducing independence when exhibited excessively. Moral reasoning proves to strengthen auditor integrity and serves as a protective mechanism against opportunistic behavior, whereas moral disengagement weakens the oversight function and increases audit risk. The effectiveness of auditors as "guardians" depends on the dynamic interaction between narcissistic traits, moral reasoning capacity, internal controls, and organizational context.